2022
DOI: 10.2478/jcbtp-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

How Do Bank-Specific Factors Impact Non-Performing Loans: Evidence from G20 Countries

Abstract: Banking is important for the stability and success of the economy. The success of the banking system on financial intermediation in developing countries is directly affected by non-performing loans (NPLs). Many factors can be treated as NPL determinants. Accordingly, the factors that explain NPLs contain very important information for banks. To this end, the study is an attempt to examine various banking factors that affect NPLs with respect to developing economies. In this study, the bank-specific and macroec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…We further examine the impact of the peer effect of those specified banks mentioned above on non‐performing loans. Referring to some of previous studies (e.g., Akins et al, 2016; Beck et al, 2006; Erdas & Ezanoglu, 2022; Radivojevic & Jovovic, 2017), we specify the empirical models as NPLri,tgoodbreak=α0goodbreak+α1italicyeargoodbreak+α2NPLri,t1goodbreak+α3PEi,t1goodbreak+α4BIGi,t1goodbreak+α5BIGi,t1goodbreak×PEi,t1goodbreak+α6SMALLi,t1goodbreak+α7SMALLi,t1goodbreak×PEi,t1goodbreak+α8TAi,t1goodbreak+α9ROAi,t1goodbreak+α10NIMi,t1goodbreak+α11SRi,t1goodbreak+α12CARi,t1goodbreak+α13LLRi,t1goodbreak+ei,t NPLri,tgoodbreak=β0goodbreak+β1italicyeargoodbreak+β2NPLri,t1goodbreak+β3PEi,t1goodbreak+β4HPi,t…”
Section: Empirical Analysismentioning
confidence: 89%
“…We further examine the impact of the peer effect of those specified banks mentioned above on non‐performing loans. Referring to some of previous studies (e.g., Akins et al, 2016; Beck et al, 2006; Erdas & Ezanoglu, 2022; Radivojevic & Jovovic, 2017), we specify the empirical models as NPLri,tgoodbreak=α0goodbreak+α1italicyeargoodbreak+α2NPLri,t1goodbreak+α3PEi,t1goodbreak+α4BIGi,t1goodbreak+α5BIGi,t1goodbreak×PEi,t1goodbreak+α6SMALLi,t1goodbreak+α7SMALLi,t1goodbreak×PEi,t1goodbreak+α8TAi,t1goodbreak+α9ROAi,t1goodbreak+α10NIMi,t1goodbreak+α11SRi,t1goodbreak+α12CARi,t1goodbreak+α13LLRi,t1goodbreak+ei,t NPLri,tgoodbreak=β0goodbreak+β1italicyeargoodbreak+β2NPLri,t1goodbreak+β3PEi,t1goodbreak+β4HPi,t…”
Section: Empirical Analysismentioning
confidence: 89%
“…The impact of loan growth on loan loss is mixed, according to empirical findings. However, most studies show a positive impact, as reported by Hess et al (2009), Foos et al (2010, Amador et al (2013), Vithessonthi (2016), Ibrahim and Rizvi (2018), Dang (2019), Bhowmik and Sarker (2021) and Erdas and Ezanoglu (2022) for banks in various countries and regions. A few studies found an insignificant or negative impact, such as Kuzucu and Kuzucu (2019), Laeven andMajnoni (2003), Abedifar et al (2018), Koju et al (2018), andNaili andLahrichi (2022).…”
Section: Literature Review and Hypothesis Development 21 Loan Growth ...mentioning
confidence: 93%
“…Bank Specific Factor merupakan indikator yang berkaitan dengan kondisi internal perbankan itu sendiri terkait risiko bank seperti likuiditas, rentabilitas dan permodalan. Penelitian mengenai Bank Specific Factor telah banyak dilakukan, namun menggunakan proksi yang berbeda-beda dan terus berkembang dalam mengukur Bank Specific Factor (Erdas & Ezanoglu, 2022). Khan et al (2023) menyimpulkan bahwa pertumbuhan pinjaman berpengaruh positif terhadap NPL untuk perbankan konvensional, sedangkan untuk perbankan syariah pertumbuhan pinjaman memiliki pengaruh negatif terhadap NPL.…”
Section: Pendahuluanunclassified